The Cut-glass Bowl and other Stories - Fitzgerald F. S. F. Scott (Macmillan Guided Readers. Classics)
Five short stories set in America in the 1920s and 1940s. The Cut Glass Bowl, Bernice Bobs Her Hair, Gretchen`s Forty Winks, Magnetism and Three Hours Between Planes.